Is It True That Intravesical Prostatic Protrusion Affects The International Prostatic Symptom Score In Patients With Benign Prostate Enlargement? - Farras Arsyi Addaruqutni; Ana Majdawati; Bernardus Bona Wisesa; Ageng Setya Budi Mazaya (Jurnal EduHealth, 2023)
Benign Prostatic Hyperplasia (BPH), also known as benign prostate enlargement, is among the most common benign tumors affecting men, with a prevalence and incidence that increases with age, categorized as one of the genitourinary issues. In Indonesia, there are 9.2 million reported cases of BPH in men over 60 years old. Intravesical Prostatic Protrusion (IPP) is one manifestation of Benign Prostatic Hyperplasia (BPH) development. Patient complaints associated with Benign Prostatic Hyperplasia (BPH) can be assessed through the International Prostatic Symptom Score (IPSS). This study aims to investigate the potential relationship between Intravesical Prostatic Protrusion (IPP) and patient complaints assessed by the International Prostatic Symptom Score (IPSS) in individuals diagnosed with BPH. This research employed an observational cross-sectional study design and utilized the chi-square correlation test. Data from 67 Benign Prostatic Hyperplasia (BPH) patients, all displaying prostate protrusion, were categorized into three groups based on the degree of protrusion observed on prostate ultrasound: grade I, grade II, and grade III. IPSS scores were measured using the Indonesian version of the IPSS questionnaire, where patients self-assessed their symptoms and were categorized into mild, moderate, or severe groups. Analysis using the chi-square correlation test revealed a p-value of 0.208, signifying the obtained p-value > 0.05. This suggests that no statistically significant relationship was found between the variables under investigation. The study concludes no significant relationship exists between Intravesical Prostatic Protrusion (IPP) and the International Prostatic Symptom Score (IPSS) in individuals diagnosed with Benign Prostatic Hyperplasia (BPH).